The association of the Bolsa Familia Program with children's oral health in Brazil - Paola Calvasina; Patricia O'Campo; Mateus Mota Pontes; Jamille Barreto Oliveira; Anya P G F Vieira-Meyer (BMC, 2018)
Abstract Background Several studies have demonstrated that Conditional Cash Transfer (CCT) programs reduce poverty/inequity and childhood mortality. However, none of these studies investigated the link between CCT programs and children's oral health. This study examines the association between receiving the Brazilian conditional cash transfer, Bolsa Familia Program (BFP), and the oral health of five-year-old children in the Northeast of Brazil. Methods We conducted a cross-sectional study with 230 caregivers/children randomly selected in primary health care clinics in the city of Fortaleza in 2016. Interviews and oral health examinations were performed. Descriptive statistics and multiple logistic regression analyses were conducted to identify factors associated with dental caries among five-year-old children enrolled in the BFP. Results Around 40% of children enrolled in the BFP had dental caries. However, those who received Bolsa Familia (BF) for a period up to two years (OR = 0.13, 95% CI 0.05-0.35) had substantially lower adjusted odds of having dental caries than those who had never received BF. In addition, the association of BF and dental caries was more prominent among extremely poor families (OR = 0.05, 95% CI 0.01-0.28). Conclusions Although initial enrolment in the BFP predicted low dental caries among five-year-old children, the prevalence of dental caries in this population is still high, thus, public health programs should target BF children's oral health. An ongoing effort should be made to reduce oral health inequalities among children in Brazil.